2011
DOI: 10.1038/hr.2011.143
|View full text |Cite
|
Sign up to set email alerts
|

Cilnidipine, but not amlodipine, ameliorates osteoporosis in ovariectomized hypertensive rats through inhibition of the N-type calcium channel

Abstract: Both osteoporosis and high blood pressure are major diseases in aging populations. Recent studies demonstrated that some antihypertensive drugs reduced the risk of bone fracture in elderly patients. Although calcium channel blockers (CCB) are widely used as first-line antihypertensive agents, there is no evidence that they prevent osteoporosis. In this study, we investigated the effects of two types of CCB on bone metabolism: cilnidipine (L-/N-type CCB), which suppresses norepinephrine release from the sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…In the present study, UUO rats were treated with cilnidipine or amlodipine at the dose of 3 mg·kg Ϫ1 ·day Ϫ1 for 14 days. Several previous reports demonstrated that cilnidipine and amlodipine had a lowering effect of blood pressure to a similar extent at the dose used in this study (3 mg·kg Ϫ1 ·day Ϫ1 ) in hypertensive rats (12,25,26). Previous pharmacological study also demonstrated that cilnidipine and amlodipine inhibited L-type Ca channel current to a similar extent using a whole cell patch-clamp technique (29).…”
Section: Discussionmentioning
confidence: 49%
“…In the present study, UUO rats were treated with cilnidipine or amlodipine at the dose of 3 mg·kg Ϫ1 ·day Ϫ1 for 14 days. Several previous reports demonstrated that cilnidipine and amlodipine had a lowering effect of blood pressure to a similar extent at the dose used in this study (3 mg·kg Ϫ1 ·day Ϫ1 ) in hypertensive rats (12,25,26). Previous pharmacological study also demonstrated that cilnidipine and amlodipine inhibited L-type Ca channel current to a similar extent using a whole cell patch-clamp technique (29).…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, amlodipine alleviated the reduction in femur bone density in stroke-prone spontaneously hypertensive rats (20). However, in another study, amlodipine showed no action on bone metabolism in ovariectomized hypertensive rats (21). Despite the convincing evidence given above, there are hardly enough data about the effects of CCB use on bone physiology in humans.…”
Section: Discussionmentioning
confidence: 84%
“…Some authors in the literature have described the effect of AML, whose effect on bone tissue we considered. The anti-osteoporotic effect of AML may result from the blocking of L-type calcium channels, by stimulating inositol triphosphate receptors, by releasing intracellular calcium, or by stopping the activation and maturation of osteoclasts [18]. Shimizu et al [18] demonstrated the positive effect of another CCB cilnidipine, mediated not only by the ­L-type but also by the N-type calcium channel.…”
Section: Discussionmentioning
confidence: 99%
“…The ­N-type calcium channel is thought to be involved in catecholamine release. Accordingly, the N/L-type CCB has a probability of less activation of the renin-angiotensin system [18]. Moreover, the administration of AML suppresses an inflammatory response by reducing the production of TNF-alpha, IL-1beta, and IL-6 [19], all of which are osteoclastogenic [20, 21].…”
Section: Discussionmentioning
confidence: 99%